Growth of proton conducting strontium cerate composites - SHILPA, C. K.; JASIRA, S. V.; VEENA, V. P.; NISSAMUDEEN, K. M. (Journal of Metals, Materials and Minerals, 2023)
The increased population and modern way of life have greatly depleted the effectiveness of traditional energy production methods. There is a strong demand for environmentally friendly and renewable alternatives to replace the old systems. Sustainable energy production systems have emerged as a vital replacement for the conventional use of fossil fuels. Among these, solid oxide fuel cells (SOFCs) play a significant role. Recently, researchers have developed electrolyte components for SOFCs using proton-conducting perovskites with excellent conductivity. This critical assessment presents a yearly overview of innovative strategies for utilizing doped strontium cerate perovskites in energy production systems, a novel approach. The importance of identifying dopants that can enhance conductivity and stability in strontium cerate composites is emphasized, creating a crucial element for high-performance energy systems. Through a comparative study, it's been found that rare earth elements with smaller ionic radii, such as thulium-doped strontium cerium zirconate in an additional composite form, can outperform the traditionally used ytterbium-doped strontium cerate composites in proton-conducting applications.